Telaah Perkembangan Kognitif Anak Madrasah Ibtidaiyah Pada Masa Pandemi - Salim Hasan (Universitas Muslim Indonesia, 2021)
Cognitive development shows the characteristics of children's intelligence. This is an aspect of the development of children's intelligence at all levels of education. Education must provide space for children's intelligence growth through responsive learning to children's potential. The pandemic period has had an impact on the child's cognitive development system, it is realized that there are positive things but there are also negative symptoms that must be studied and taken into account in the future. The results of the discussion of this paper conclude that; First, children's cognitive development is a mental process that encourages the formation of behavioral changes. This development generally refers to aspects of children's intelligence so as to encourage them to acquire new skills in receiving, storing information, and then being able to use it in life. The process of cognitive development lasts from birth until a human dies. Second, the cognitive development of Madrasah Ibtidaiyah children during the pandemic can be optimized by creating a conducive learning environment by understanding children, providing children's play space, and parents and teachers realizing that children are not half adults, children are in the imitating phase. learning. The assistance provided must still provide space for children to remain creative which is avoided from the pressure and coercion of studying at home. Knowledge of children's development during the pandemic is needed to further maximize children's cognitive development at Madrasah Ibtidaiyah.